Human uroporphyrinogen III synthase: molecular cloning, nucleotide sequence, and expression of a full-length cDNA. - Tsai, S F (1988)
Uroporphyrinogen III synthase [URO-synthase; hydroxymethylbilane hydro-lyase (cyclizing), EC 4.2.1.75], the fourth enzyme in the heme biosynthetic pathway, is responsible for conversion of the linear tetrapyrrole, hydroxymethylbilane, to the cyclic tetrapyrrole, uroporphyrinogen III. The deficient activity of URO-synthase is the enzymatic defect in the autosomal recessive disorder congenital erythropoietic porphyria. To facilitate the isolation of a full-length cDNA for human URO-synthase, the human erythrocyte enzyme was purified to homogeneity and 81 nonoverlapping amino acids were determined by microsequencing the N terminus and four tryptic peptides. Two synthetic oligonucleotide mixtures were used to screen 1.2 x 10(6) recombinants from a human adult liver cDNA library. Eight clones were positive with both oligonucleotide mixtures. Of these, dideoxy sequencing of the 1.3 kilobase insert from clone pUROS-2 revealed 5' and 3' untranslated sequences of 196 and 284 base pairs, respectively, and an open reading frame of 798 base pairs encoding a protein of 265 amino acids with a predicted molecular mass of 28,607 Da. The authenticity of this clone was established by colinearity of the predicted amino acid sequence with 81 microsequenced residues from the purified enzyme. In addition, high levels of enzymatic activity and immunoreactive protein were expressed when a blunt-ended 971-base-pair Ava II cDNA fragment containing the entire coding region was inserted into vectors for expression in Escherichia coli. The isolation and expression of this full-length cDNA for human URO-synthase should facilitate studies of the structure, organization, and chromosomal localization of this heme biosynthetic gene as well as the characterization of the molecular lesions causing congenital erythropoietic porphyria.